Liberalization, Technology Adoption, and Stock Returns : Evidence from Telecom - Arezki, Rabah (World Bank, Washington, DC, 2021)
The paper investigates the pace of technology adoption in telecom technology post liberalization and its effect on stock returns using a new global panel data set. The results are twofold. First, the evidence points to the complementarity between telecom liberalization and regulatory independence in driving a sustained pace of technology adoption. Second, the results show a positive and economically significant effect of telecom adoption on stock returns, pointing to significant spillovers of telecom to the rest of the economy.